25 years of multiple stressors driving the coral-algae phase shift in Akumal, Mexico. (15th November 2021) - Randazzo-Eisemann, Ángela; Garza-Pérez, Joaquín Rodrigo; Penié-Rodriguez, Iván; Figueroa-Zavala, Baruch
Abstract: Interactions between multiple stressors (climate change, pollution, and overfishing) can erode ecological thresholds and trigger a phase shift from a coral-dominated reef state to less desired benthic states. Akumal Reef located in the North of the Mexican Caribbean is an important case study to quantify the ecological changes of coral reefs affected by multiple stressors. Here we used both field data (benthic cover, coral condition, fish biomass), together with satellite data of the main stressors (degree heating weeks, chlorophyll a, and urban area), to (i) reconstruct the timeline of stressors that have affected Akumal Reef from 1995 to 2019; (ii) describe the changes in coral reef components (benthic cover, bleaching, coral diseases, and fish biomass) in this period; and (iii) propose a model integrating coral benthic changes and the significant stressors influencing those changes through time while taking into account stressors interactions and partial effects. Our results show that between 1995 and 2019, hard coral cover suffered an average absolute loss of 84%. This loss contrasted with an average absolute gain in total algae cover of 74% and was negatively associated with an increase of 290% in the urban area. During the study period, there has been no signal of positive recovery in hard coral cover, and increasingly available space has been occupied alternatively by filamentous algae or macroalgae after acute stressor events, such as bleaching or disease, which are more frequent, and persistent in the last decade. Our integrative model highlights interactions between urban area, maximum degree heating weeks, and chlorophyll a as main drivers of hard coral decrease, as well as interactions between urban area and precipitation, related to total algae increase. Akumal Reef degradation trend must be rapidly addressed by implementing management tools integrated into a comprehensive coastal planning model, which must reduce pollution and overfishing, allowing the recovery of its structure and function, and providing persistence of ecosystem services in a context of global changes and ecological 'surprises'. Highlights: Synergy of multiple stressors erode reef resilience, increasing vulnerability. Akumal Reef loss of 84% in hard coral is related to coastal urbanization. Phase-shift in Akumal could be more related to nutrients than to herbivores loss. Benthic dominance shifts alternatively from filamentous to macroalgae after stressors. Akumal Reef requires additional management tools for integrated coastal planning.